Hubungan Usia dan Paritas dengan Kejadian Anemia pada Ibu Hamil Trimester I: Relationship Between Maternal Age and Parity and the Incidence of Anemia Among First-Trimester Pregnant Women - Atmiyati, Siti Salamatul Janah; Wulandatik, Darmayanti; Fathony, Zaiyidah; Rahmah, Afiatun; Mahfuzhah, Neneng (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Anemia in pregnancy remains a widespread public health problem, including in the working area of Alalak Selatan Public Health Center, Banjarmasin City, which previously recorded an increase in cases. Demographic factors such as maternal age and parity are theoretically believed to be risk factors triggering a decrease in hemoglobin levels. This study aimed to analyze the relationship between age and parity with the incidence of anemia in first-trimester pregnant women in the working area of Alalak Selatan Public Health Center, Banjarmasin City. This study utilized a quantitative analytic observational design with a cross-sectional approach. The sample consisted of 120 first-trimester pregnant women selected using a purposive sampling technique based on data from January to November 2025. The independent variables were age and parity, while the dependent variable was the incidence of anemia. Data were collected using observation sheets referring to the maternal cohort medical records to record age, parity, and hemoglobin levels, which were then analyzed using the Chi-Square statistical test. The results showed that the majority of respondents were in the healthy or not-at-risk reproductive age range of 20-35 years (81.7%) and had multipara parity status (48.3%). The incidence of anemia was very low, with 95% of respondents not experiencing anemia and only 5% experiencing mild anemia. Statistical tests proved that there was no significant relationship between maternal age and the incidence of anemia (p = 0.492), and no significant relationship was found between parity and the incidence of anemia (p = 0.712). This study concludes that age and parity have no relationship with the incidence of anemia in pregnant women in the area. The low rate of anemia in both at-risk and not-at-risk age and parity groups indicates that pregnant women's compliance with routine Antenatal Care (ANC) programs and iron supplementation consumption has a much more dominant impact in preventing blood deficiency complications.